PERLINDUNGAN HUKUM TERHADAP KONSUMEN YANG MEMPEROLEH UANG PALSU DALAM LAYANAN MONEY CHARGER BERDASARKAN KITAB UNDANG-UNDANG HUKUM PERDATA - Rizka Ananda Putri Aji; Hafizah Syafri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The negative impact that arises from globalization, namely the loss of Indonesian values and culture due to the entry of foreign cultures such as South Korean culture through music and dramas that are popular in Indonesia. In addition, Indonesian people tend to prefer abroad for health and education because it is considered more advanced and sophisticated, this has an impact on the increasing use of foreign exchange as a means of payment in Indonesia. Therefore, this article discusses legal protection for consumers who receive counterfeit money in money charger services based on the Indonesian Civil Code. The purpose of this study is to determine the phenomenon of consumers receiving counterfeit money at Money changer services in Indonesia and to determine the legal protection of consumers who receive counterfeit money at Money changer services based on the Civil Code. This type of research uses normative methods, data collection using primary, secondary and tertiary legal materials.